VERIFICATION METHOD FOR DISCRETE-EVENT SIMULATION BASED ON DISCRETE-EVENT SYSTEM FORMALISM - Jang, Sooyoung; Choi, Changbeom (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
As simulation models become more complex, their requirement specifications also become more complicated and difficult to verify. This study proposes requirement modeling and verification methods using discrete event systems based on a discrete event system formalism. This process involves describing the requirements, translating them into a requirement model, and verifying whether the target system satisfies them. The benefits include automated verification and simplified event monitoring using a discrete event system formalism. The main contributions of this study are the proposed requirement discrete event system model, the logic and translation method, and the verification process. In addition, this study introduces the requirements for engagement simulation with multiple agents and its discrete event system model as a case study.